Dynamics of Trademark Dilution: Issues and Challenges in India and USA - Ghose, Anuttama; Ali, S.M. Aamir (Kathmandu School of Law Review, 2020)
Trademarks of an establishment cannot solely be associated with identification of origin or source. It performs an imperative task of building brand name and value. The dilution theory rejects the opinion that the role of a trademark is solely based on the recognition of the root or source of its origin and that it is not only a figurative representation but carries a creative aspect as well. For the most recent decade, the greatest inquiry in trademark law has been the manner by which to demonstrate weakening or dilution. Dilution has turned out to be a dauntingly slippery idea. The principal issue with dilution law is that it gives a cure without a supportable hypothesis of the harm or damage. Even though lately the concept has been recognized in International as well as domestic jurisdiction putting an immense responsibility on domestic jurisdiction to protect trademarks against dilution, very little has been discussed or clarified regarding the theory of dilution. Ambiguity of such nature facilitated this research trying to spot some light on the theory of dilution comparing it from divergent angles in different jurisdictions. The paper also highlights the interpretation mechanism of the courts of the dilution provision and explains the concept further with reference to important cases under the U.S. laws and European judgments in the context of the Dilution laws and draws a comparative analysis of the effectiveness of the legal framework present in India with that of the USA.